Methodical approach to the assessment of the level of threats to civilians in the case of the use of small arms on unmanned aerial vehicles - Mirnenko, Volodymyr; Novichenko, Sergii; Doska, Oleksandr; OpenʹkoPavlo; Avramenko, Oleksandr (Social Development and Security, 2020)
The results of the research published in the article will be useful for leaders of all levels of military personnel responsible for ensuring the safety of civilians in the use of weapons. The article discusses a methodical approach to assessing the level of threats to civilians in the case of unmanned aerial vehicles (UAVs). Analyzed existing documents regulating the use of small arms, it was found that the issue of safety of civilians in the firing of air targets they were not considered, which allowed to determine the unresolved scientific problem, which is to form a methodological approach to assessing the level of threats to civilians in the case of use small arms on UAV. The scientific substantiation of the probability of accidental hit of a bullet into a person, located at a certain distance from the arrow when firing on UAV, is offered. As an indicator of assessing the level of threats to civilians in the use of small arms under the UAV, the use of the indicator “the probability of accidentally hitting a bullet into a person” is justified. The method of estimation of threats to the civilian population which is based on imitation modeling of process of flight of a ball in a vertical plane, the basis of which is the algorithm of determination of probability of accidental hit of a ball into a person, which allows, depending on kinetic energy of a ball, to calculate probability of accidental and accidental probability. The calculated ratios are presented, which allow, depending on the kinetic energy of the ball, to calculate the probability of accidental killing and the probability of accidentally injuring a person. Using the capabilities of simulation it is proposed to set the probability of human damage, depending on the angles of the shot, which will justify the restrictions during firing of UAVs with small arms. On the basis of the proposed methodological approach, the directions of further researches on determination of the probability of accidental hit of a bullet in a person during firing of regular weapons of calibers from 5,45 mm and 12,7 mm on air targets of the UAV type will be determined, which will allow to take measures to ensure a minimum level of threats civilians.